ONLINE FLIPPED CLASSROOM OF INSTRUCTION ON EFL STUDENTS’ READING COMPREHENSION DURING COVID-19 - Ardiansyah, Welly; Rosyidin, Iskandar; Aimi; Suroso; Asyari, Lutfi (Department of English Education, Universitas Panca Sakti Bekasi, 2022)
The online flipped classroom is growing in popularity as the COVID-19 pandemic continues to spread throughout the world. This type of learning is necessary in many places where traditional classrooms are not possible or safe to attend. To examine the effects of the OFC model, this study used a quasi-experimental design. Moreover, this study aimed to identify English language students’ attitudes toward the OFC model of instruction. There were sixty-five students of classes XIC and XID at MAN 3 Palembang that were split into experimental and control groups randomly. The control group was treated with Blended Learning, while the experimental group was treated with Online Flipped classroom. Mixed-method design was carried out in this research. To ensure homogeneity and normality, both groups took a reading comprehension pre-test at the beginning of the study. After the experiment, the post-test was given to the experimental and control groups. The statistical analyses of independent samples t-test showed that the experimental group had better reading comprehension scores than the control group. The results of frequency analyses showed that EFL students in the experimental group had more positive attitude towards OFC model of instruction and agreed that it was helpful to them in many ways. It is suggested that OFC can be used as an effective methodology for teaching reading comprehension to EFL students.